2007
DOI: 10.1111/j.1365-2559.2007.02622.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of TopBP1 in breast cancer

Abstract: For the first time this report demonstrates aberrant expression of the TopBP1 protein in breast carcinoma. We propose TOPBP1 as a breast cancer susceptibility gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 25 publications
(56 reference statements)
2
36
0
Order By: Relevance
“…Going and colleagues reported that TopBP1 is aberrantly localized to cytosol in some areas of certain breast cancer cases (out of 61 cases examined, 37 had predominantly nuclear staining, two had undetectable staining, 13 had a nuclear and nuclear-plus-cytoplasmic pattern, and nine had a nuclear-pluscytoplasmic and purely cytoplasmic pattern [10]). We also performed immunohistochemical staining on 20 formalin-fixed paraffin-embedded breast tissue sections chosen randomly from the TopBP1-overexpressing group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Going and colleagues reported that TopBP1 is aberrantly localized to cytosol in some areas of certain breast cancer cases (out of 61 cases examined, 37 had predominantly nuclear staining, two had undetectable staining, 13 had a nuclear and nuclear-plus-cytoplasmic pattern, and nine had a nuclear-pluscytoplasmic and purely cytoplasmic pattern [10]). We also performed immunohistochemical staining on 20 formalin-fixed paraffin-embedded breast tissue sections chosen randomly from the TopBP1-overexpressing group.…”
Section: Resultsmentioning
confidence: 99%
“…Although some cells have cytoplasmic staining in addition to intense nuclear staining, we have not observed exclusively cytoplasmic distribution in these sections. To ensure that a difference in antigen retrieval techniques did not result in a different apparent distribution of TopBP1, tissues from random cases were stained separately with antigen retrieval using pH 6.0 citrate (used in the study by Going et al [10]) or pH 9.0 EDTA. The staining was less with citrate than with EDTA, but both methods demonstrated primarily nuclear patterns with little cytoplasmic staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2003) showed that deletion of the BRCT7-8 and NLS region of TopBP1 induces cytoplasmic localization of the protein. Aberrant expression and intracellular localization of TopBP1 is observed immunohistochemically in breast cancer (Going et al, 2007).…”
Section: Fig 2 Topbp1 Functional Domains and Sites Of Interacting Pmentioning
confidence: 99%
“…The carboxyl-terminal region of TopBP1 containing two BRCT domains shows considerable similarity to the corresponding part of BRCA1 (Going et al, 2007;Karppinen et al, 2006;Makiniemi et al, 2001;Morris et al, 2009;Yamane et al, 1997Yamane et al, , 2003. Apart from structural similarity TopBP1 shares many other common features with BRCA1.…”
Section: Fig 2 Topbp1 Functional Domains and Sites Of Interacting Pmentioning
confidence: 99%
See 1 more Smart Citation